Host microRNAs are decreased in pediatric solid-organ transplant recipients during EBV+ Post-transplant Lymphoproliferative Disorder - Sen, Ayantika; Enriquez, Jeanna; Rao, Mahil; Glass, Marla; Balachandran, Yarl; Syed, Sharjeel; Twist, Clare J.; Weinberg, Kenneth; Boyd, Scott D.; Bernstein, Daniel; Trickey, Amber W.; Gratzinger, Dita; et al. (Frontiers in Immunology, 2022)
Post-transplant lymphoproliferative disorder (PTLD) is a serious complication of solid organ transplantation. Predisposing factors include primary Epstein-Barr virus (EBV) infection, reactivation of EBV in recipient B cells, and decreased T cell immunity due to immunosuppression. In our previous studies, EBV infection was demonstrated to markedly alter the expression of host B cell microRNA (miR). Specifically, miR-194 expression was uniquely suppressed in EBV+ B cell lines from PTLD patients and the 3’untranslated region of IL-10 was determined to be targeted by miR-194. Although EBV has been shown to regulate host miR expression in B cell lymphoma cell lines, the expression of miRs in the circulation of patients with EBV-associated PTLD has not been studied. The objective of this study was to determine if changes in miR expression are associated with EBV+ PTLD. In this study, we have shown that miR-194 is significantly decreased in EBV+PTLD tumors and that additional miRs, including miRs-17, 19 and 106a are also reduced in EBV+PTLD as compared to EBV-PTLD. We quantitated the levels of miRs-17, 19, 106a, 155, and 194 in the plasma and extracellular vesicles (EV; 50-70 nm as determined by nanoparticle tracking analysis) from pediatric recipients of solid organ transplants with EBV+ PTLD+ that were matched 1:2 with EBV+ PTLD- pediatric transplant recipients as part of the NIH-sponsored Clinical Trials in Organ Transplantation in Children, (CTOTC-06) study. Levels of miRs-17, 19, 106a, and 194 were reduced in the plasma and extracellular vesicles (EV) of EBV+ PTLD+ group compared to matched controls, with miRs-17 (p = 0.034; plasma), miRs-19 (p = 0.029; EV) and miR-106a (p = 0.007; plasma and EV) being significantly reduced. Similar levels of miR-155 were detected in the plasma and EV of all pediatric SOT recipients. Importantly, ~90% of the cell-free miR were contained within the EV supporting that EBV+ PTLD tumor miR are detected in the circulation and suggesting that EVs, containing miRs, may have the potential to target and regulate cells of the immune system. Further development of diagnostic, mechanistic and potential therapeutic uses of the miRs in PTLD is warranted.